Associations of Slow-Wave Sleep With Prevalent and Incident Type 2 Diabetes in the Multi-Ethnic Study of Atherosclerosis - Sina Kianersi; Susan Redline; Morgana Mongraw-Chaffin; Tianyi Huang (The Journal of Clinical Endocrinology & Metabolism, 2023)
Abstract Context N3 sleep (i.e., slow-wave sleep), a marker of deep restorative sleep, is implicated in hormonal and blood pressure regulation and may impact cardiometabolic health. Objective We conducted cross-sectional and prospective analyses to test whether a higher proportion and longer duration of N3 sleep are associated with reduced type 2 diabetes risk. Methods A subsample of participants from the Multi-Ethnic Study of Atherosclerosis completed 1-night polysomnography at Exam 5 (2010-2013) and were prospectively followed until Exam 6 (2016-2018). We used modified Poisson regression to examine the cross-sectional associations of N3 proportion and duration with prevalent diabetes and Cox proportional hazards models to estimate risk of diabetes according to N3 measures. Results In cross-sectional analyses (n = 2026, mean age: 69 years), diabetes prevalence was 28% (n = 572). Compared with the first quartile (Q1) of the N3 proportion (<2.0%), participants in Q4 (≥15.4%) were 29% (95% CI 0.58, 0.87) less likely to have prevalent diabetes (P trend = .0016). The association attenuated after adjustment for demographics, lifestyles, and sleep-related factors (P trend = .3322). In prospective analyses of 1251 participants and 129 incident cases over 6346 person-years of follow-up, a curvilinear relationship was observed between N3 proportion and incident diabetes risk. In the fully adjusted model, the hazard ratio (95% CI) of developing diabetes vs Q1 was 0.47 (0.26, 0.87) for Q2, 0.34 (0.15, 0.77) for Q3, and 0.32 (0.10, 0.97) for Q4 (P nonlinearity = .0213). The results were similar for N3 duration. Conclusion Higher N3 proportion and longer N3 duration were prospectively associated with lower type 2 diabetes risk in a nonlinear fashion among older American adults.